Knockout of CAFFEOYL-COA 3-O-METHYLTRANSFERASE 6/6L enhances the S/G ratio of lignin monomers and disease resistance in Nicotiana tabacum - Liu, Mingxin; Liu, Huayin; Zhang, Jianduo; Li, Cui; Li, Yinke; Yang, Guangyu; Xia, Tong; Huang, Haitao; Xu, Yong; Kong, Weisong; Hou, Bingzhu; Qi, Xiaoquan; et al. (Frontiers in Plant Science, 2023)
Background: Nicotiana tabacum is an important economic crop, which is widely planted in the world. Lignin is very important for maintaining the physiological and stress resistant functions of tobacco. However, higher lignin content will produce lignin gas, which is not conducive to the formation of tobacco quality. To date, how to precisely fine-tune lignin content or composition remains unclear.Results: Here, we annotated and screened 14 CCoAOMTs in Nicotiana tabacum, and obtained homozygous double mutants of CCoAOMT6 and CCoAOMT6L through CRSIPR/Cas9 technology. The phenotype showed that the double mutants have better growth than the wild-type, while the S/G ratio increased and the total sugar decreased. Resistance against pathogens test and the extract inhibition test showed the transgenic tobacco has stronger resistance to tobacco bacterial wilt and brown spot disease, which are infected by Ralstonia solanacearum and Alternaria alternata respectively. The combined analysis of metabolome and transcriptome in the leaves and roots suggested that the changes of phenylpropane and terpene metabolism are mainly responsible for these phenotype. Further, the molecular docking indicated that the up-regulated metabolites, such as soyasaponin Bb, improves the disease resistance due to highly stable binding with tyrosyl-tRNA synthetase targets in Ralstonia solanacearum and Alternaria alternata. Conclusions: CAFFEOYL-COA 3-O-METHYLTRANSFERASE 6/6L can regulate the S/G ratio of lignin monomers, and may affect tobacco bacterial wilt and brown spot disease resistance by disturbing phenylpropane and terpene metabolism in leaves and roots of Nicotiana tabacum, such as soyasaponin Bb.